Carotid artery intima–media thickness in non-diabetic hypertensive patients and their correlation with microalbuminuria: A cross-sectional study - Bhusal, Khema Raj; Khanal, Umesh; Pathak, Surya; Khanal, Pratik; Bhattarai, Madhur; Gyanwali, Pradip; Simkhada, Rabindra; Oli, Krishna Kumar (Nepalese Heart Journal, 2025)
Background: Carotid artery intima-media thickness (IMT) is an early indicator of atherosclerosis and a predictor of cardiovascular disease. Hypertension, prevalent globally, is linked to metabolic risk factors and damages carotid artery characteristics. Microalbuminuria signals endothelial dysfunction, increasing the risk of stroke and cardiovascular events. Objective: The objective of the study was to determine the prevalence of carotid artery changes in non-diabetic hypertensive patients and its correlation with microalbuminuria. Methods: A quantitative cross-sectional study was done in 107 participants diagnosed as non-diabetic hypertensive patients visiting Manmohan Memorial medical college and Teaching hospital and Manmohan Cardio-thoracic Vascular and transplant Centre from January 2020 to August 2020. Carotid IMT was measured using B-mode ultrasound, and microalbuminuria was assessed by spot urine albumin-to-creatinine ratio. Data were analyzed using chi-square test and Pearson correlation. Results: The prevalence of abnormal carotid artery IMT is 16.8% and microalbuminuria is 26.2%. No significant association was found between IMT status and micro-albuminuria status (p=0.315). Additionally, there was no significant correlation between IMT and urine albumin level (r=-0.167, p=0.086). Conclusions: The level of microalbuminuria was similar in non-diabetic hypertensive patients, whether or not they had carotid artery changes. However, there was no significant difference between the two groups.